Degradation kinetics of Andrographolide in aqueous solution, product identification and biological activity evaluation - Jaidee, Wuttichai; Rujanapun, Narawadee; Malee, Kulawadee; Chaisawadi, Suchada; Puttarak, Panupong; Hiransai, Poonsit; Cordell, Geoffrey A; Sarker, Satyajit D; Nahar, Lutfun; Charoensup, Rawiwan (Scientific reports, 2025)
Andrographolide (1) is a labdane-type diterpene lactone and the major bioactive metabolite (2.39%) in the leaves of Andrographis paniculata (Acanthaceae). To further explore its stability, the thermal degradation kinetics of compound 1 at pH 2.0, pH 6.0, and pH 8.0 were modeled at three temperatures within 50-85 °C. The activation energy (Ea), shelf-life (t90%), and rate constant (k) for compound 1 were determined using the Arrhenius equation. Consequently, the results indicated that degradation followed first-order kinetics, and the optimum pH for stability was determined to be between pH 2.0 and 4.0. Major degradation products formed under pH 2.0 and pH 6.0 conditions were isolated and spectroscopically characterized by comparison with known compounds. Under pH 2.0 conditions, two degradation products were identified: isoandrographolide (2) and 8,9-didehydroandrographolide (3). Under pH 6.0 conditions, three degradation products were formed: 15-seco-andrographolide (4), 14-deoxy-15-methoxyandrographolide (5), and 11,14-dehydro-14-deoxyandrographolide (6). Anti-inflammatory and cytotoxicity assessments demonstrated reduced biological effects for the degradation products compared with compound 1. This highlights the importance of controlling pH during formulation to ensure product stability, sustained bioactivity, and patient benefit.
Keywords: stabilita léku; Diterpenes; Animals; antiflogistika; Kinetics; Andrographolide; Hydrogen-Ion Concentration; teplota; listy rostlin; Arrhenius equation; lidé; NO production; Mice; Plant Leaves; Degradation; Drug Stability; myši; voda; Temperature; Water; pH dependency; Anti-Inflammatory Agents; Product characterization; zvířata; koncentrace vodíkových iontů; diterpeny; kinetika; Cytotoxicity; Andrographis; Humans